Preparation of a new animal glue binder for foundry use - Liu, Wei-hua; Wang, Tian-shu; Li, Ying-min; Ren, Yu-yan; Huo, Wen-hui (China foundry, 2016)
A new casting binder was prepared based on an animal bone glue. In order to overcome the disadvantages of the animal glue agglomeration at room temperature, an alkaline decomposition process was used, with acrylic acid, ammonium persulfate, and glucose as modifiers of the animal glue to obtain a high strength of binding. In the process of alkaline decomposition, Na OH was used as the catalyst with the addition of 3, 4, 5, 6, 7, 8wt.%, respectively, into 100 g of animal glue and the alkaline decomposition temperature was set for 30, 40, 50, 60, and 70 °C, with an identical decomposition time of 30 min, in order to reduce viscosity of the animal glue and maintain a liquid state at room temperature. The added acrylic acid, ammonium persulfate and glucose were determined through an orthogonal experiment. The experimental results are as fol ows： the optimal amount of NaOH addition is 5wt.%; alkaline decomposition temperature is 50 °C; the optimal weight ratio of three kinds of modifiers to animal glue is acrylic acid ： ammonium persulfate ： glucose ： animal glue = 30：3：15：100; the modification reaction should be performed at 75 °C with a reaction time of 90 min. With the addition of 3% binder to sand, a final tensile strength of about 3.36 MPa and surface tension value of about 25.387 m N·m~（-1） are achieved; the gas evolution at 850 °C is 19 ml·g~（-1） and the residual strength after high temperature（700 ■ × 10 min） is 0 MPa. Finally, the new binder was characterized and analyzed by means of element analysis and an IR infrared spectrum.